Nexus of environmental accounting, sustainable production and financial performance: An integrated analysis using PLS-SEM, fsQCA, and NCA - Md. Saheb Ali Mondal; Nazma Akter; Abdullah Mohammed Ibrahim (Environmental Challenges, 2024)
This study delves into the complex interplay of environmental accounting, sustainable production, and financial performance within the textile industry in Bangladesh. The background highlights the growing importance of sustainable practices in the business landscape and the need for empirical insights in the context of textile companies. The purpose of the study is to uncover the impact of environmental accounting practices, such as environmental cost accounting, carbon accounting, and sustainability reporting, on financial performance. Employing a comprehensive methodology that combines Partial Least Squares Structural Equation Modeling (PLS-SEM), fuzzy-set Qualitative Comparative Analysis (fsQCA), and Necessity Condition Analysis (NCA), the research provides a nuanced understanding of the intricate relationships among these variables. The results reveal that environmental accounting positively influences financial outcomes, and sustainable production acts as both a direct enhancer of financial performance and a mediator in the relationship between environmental accounting initiatives and financial success. Practical and managerial implications emphasize the strategic integration of environmental accounting practices, prioritization of sustainable production, and the role of transparency in sustainability reporting for long-term financial success. Thus, the study offers a roadmap for businesses navigating the intersection of sustainability and financial performance, contributing valuable insights for both academia and industry practitioners.